2020
DOI: 10.3390/ijerph17207441
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: Knowledge and Attitudes in Public Markets in the Former Katanga Province of the Democratic Republic of Congo

Abstract: Background. Public markets were exempted from the restrictive regulations instituted to limit the rapid spread of the COVID-19 pandemic in the Democratic Republic of the Congo (DRC). In the early stage of the pandemic, we assessed people’s knowledge, attitudes, and behavior on public markets towards COVID-19. Methods. We conducted a cross-sectional study from 16 to 29 April 2020 among sellers and customers frequenting the food sections of ten public markets in three large cities (Kolwezi, Likasi, and Lubumbash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 18 publications
4
29
3
1
Order By: Relevance
“…The included studies were all conducted in sub-Saharan Africa and published in 2020. Ten of the studies were conducted in Ethiopia [10,12,[29][30][31][32][33][34][35][36], eight in Nigeria [37][38][39][40][41][42][43][44], three in Cameroon [45][46][47], two in Uganda [9,48], one each in Rwanda [49], Ghana [50], Democratic Republic of Congo [51], Sudan [52], and Sierra Leone [53], (Fig 2). A total number of 14,353 study participants were reported in the included studies, with over half (51%) of them being males.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The included studies were all conducted in sub-Saharan Africa and published in 2020. Ten of the studies were conducted in Ethiopia [10,12,[29][30][31][32][33][34][35][36], eight in Nigeria [37][38][39][40][41][42][43][44], three in Cameroon [45][46][47], two in Uganda [9,48], one each in Rwanda [49], Ghana [50], Democratic Republic of Congo [51], Sudan [52], and Sierra Leone [53], (Fig 2). A total number of 14,353 study participants were reported in the included studies, with over half (51%) of them being males.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Only 30% of participants had correct knowledge of COVID-19%, and 98% were concerned about the increase in food insecurity associated with the lockdown measures. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, few studies of the social acceptability of measures organised by an African country using a sound conceptual approach and a national sample are available. Studies in the Democratic Republic of Congo, Egypt, or Nigeria [16][17][18]centrally addressed acceptability and did not use a sound conceptual approach. Conceptual re ections on acceptability remain as rare as their applications [19,20].…”
Section: Introductionmentioning
confidence: 99%